Integrasi Kearifan Lokal Dalam Responsivitas Tata Kelola Layanan Publik Berkalajutan Studi Ekowisata Budaya Gurabunga - Sulha, Sulha; Udin, Mediyana (Jurnal Ilmiah Wahana Pendidikan, 2026)
This article analyzes the integration of local wisdom in enhancing the responsiveness of sustainable public service governance within the development of cultural ecotourism in Gurabunga Village, Tidore Islands City. In the post-bureaucratic reform era, public services are required to move beyond procedural efficiency toward socio-cultural responsiveness that reflects local values and identities. This study employs a qualitative descriptive approach with a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis involving local government officials, traditional leaders, ecotourism actors, and community members. The findings demonstrate that local wisdom—manifested through customary deliberation, collective participation, and culturally embedded environmental ethics—plays a strategic role in strengthening policy legitimacy, improving community trust, and supporting sustainability. However, a responsiveness gap persists when public service policies are implemented in an administrative–procedural manner without substantive involvement of adat institutions. The study concludes that the integration of local wisdom is a fundamental prerequisite for achieving responsive and sustainable public service governance in cultural ecotourism areas